2013
DOI: 10.1111/j.2042-7158.2012.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D metabolism in cutaneous tumour formation and progression

Abstract: Objectives Very limited information is available on the role of vitamin D in skin carcinogenesis. For most individuals, skin cancer can be readily managed with surgery; however, some patients may face life-threatening neoplasia. Sun exposure, specifically UV radiation, is a causative agent for development of skin cancer, though, somewhat ironically, sunlight through the production of vitamin D may have protective effect against some skin cancers. This review focuses on the development and progression of cutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 96 publications
0
22
0
Order By: Relevance
“…Regarding skin cancer, epidemiological and laboratory studies suggest that vitamin D and its metabolites may have a similar protective effect. 5,7,8 In a case-control study in elderly men, Tang et al 9 found that higher levels of 25(OH)D were associated with a decreased risk of having a history of NMSC. Yet, some studies have negated this finding with an increased risk of NMSC with increased vitamin D levels, 5,10 and others were unable to demonstrate any association.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding skin cancer, epidemiological and laboratory studies suggest that vitamin D and its metabolites may have a similar protective effect. 5,7,8 In a case-control study in elderly men, Tang et al 9 found that higher levels of 25(OH)D were associated with a decreased risk of having a history of NMSC. Yet, some studies have negated this finding with an increased risk of NMSC with increased vitamin D levels, 5,10 and others were unable to demonstrate any association.…”
Section: Introductionmentioning
confidence: 99%
“…Anthracyclines (e.g. doxorubicin) are antitumor antibiotics that interfere with enzymes involved in DNA replication, independently of the phase of the cell cycle 57. Similarly, taxanes (e.g.…”
Section: Tnbc: Strategies For Diagnosis and Treatmentmentioning
confidence: 99%
“…A role for 25-hydroxyvitamin D and its receptor, VDR, has been implicated in the biology of a number of physiologic and pathophysiologic cutaneous processes including skin aging (Reichrath, 2012), wound healing (Luderer et al, 2013), psoriasis (Hoss et al, 2013), epidermal Langerhans cell functioning (Yasmin et al, 2013), and both melanoma and non-melanoma skin cancer (Nemazannikova et al, 2013). The action of 25-hydroxyvitamin D and VDR in keratinocytes may help protect against non-melanoma skin cancer by regulating cell proliferation and differentiation (Bikle et al, 2013; Lehmann, 2009).…”
Section: Introductionmentioning
confidence: 99%